Do laterality and strength asymmetry relate to preferred side in the cross-country skiing G2 skate technique - Thorrud, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Laterality, or limb dominance, is well known feature in both humans and animals. In the crosscountry skiing G2 skating technique, skiers use an asymmetrical loaded double pole push synchronous with one leg push (strong side), but without poling on the other leg push (weak side). Anecdotal evidence indicates that most elite skiers manage to use both sides without difficulties at low and medium exercise intensities. However, when the intensity increases, skiers show a greater bias towards one side. Therefore, the aim of this study was to examine whether this bias is found in elite skiers, if it is related to exercise intensity and the association with laterality, muscle strength and power asymmetry. Methods: Fifteen male cross-country skiers were tested for upper and lower body maximal strength and power on the dominant and non-dominant side in five exercises. General laterality was assessed via the Edinburgh Handedness Inventory and the Waterloo Footedness Questionnaire- Revised. Lateral preferences in the G2 technique at five different intensities, ranging from low to maximal sprinting, were assessed by a five-point scale from always left to always right. Additionally, the subjects rated how well they coped with the G2 on the preferred and non-preferred strong side on a 10-point scale at the five different intensities. Results: The degree of coping was significantly different (p<0.05) between the preferred and non-preferred strong side for all intensities. Lateral preference in the G2 was not related to either handedness (r= 0.218) or footedness (r= 0.282). Strength and power variables were not significantly different (p>0.05) between the preferred strong side and weak side. Coping of the non-preferred side decreased as intensity increased with significant differences (p<0.05) between all intensities, except for the two lowest. Discussion: The current study demonstrates a greater bias towards preferring one side in G2 skating among cross-country skiers, and that this bias increase as intensity increases. The athletes` coping of the preferred strong side remains stable across all intensities, whereas coping of the non-preferred strong side decrease. There were no clear patterns of laterality, strength or power related to the preferences in G2 skating. Thus, lateral preference in the G2 is task specific and is not related to laterality in general or the athletes` strength asymmetry.